2022
DOI: 10.3390/su141710820
|View full text |Cite
|
Sign up to set email alerts
|

How New Urbanization Affects Tourism Eco-Efficiency in China: An Analysis Considering the Undesired Outputs

Abstract: In the context of the global Sustainable Development Goals, the study of tourism eco-efficiency (TE) becomes particularly important for the balance between environmental protection and economic development in tourist destinations. This paper improves the measurement method of tourism carbon emissions, uses the Super-SBM model of undesired output to measure China’s TE, and then explores the impact of new urbanization (NU) on TE. The results show that TE in China is in dynamic equilibrium in general, the agglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…The proportion of urban population in the total population was positively correlated with tourism eco-efficiency, which is consistent with the research results of Zhang et al [13]. The city with the strongest positive influence was Cangzhou, and the surrounding cities of Cangzhou, Baoding and Xingtai, also had a strong influence.…”
Section: Analysis Of the Influencing Factors Of Tourism Eco-efficiencysupporting
confidence: 90%
See 1 more Smart Citation
“…The proportion of urban population in the total population was positively correlated with tourism eco-efficiency, which is consistent with the research results of Zhang et al [13]. The city with the strongest positive influence was Cangzhou, and the surrounding cities of Cangzhou, Baoding and Xingtai, also had a strong influence.…”
Section: Analysis Of the Influencing Factors Of Tourism Eco-efficiencysupporting
confidence: 90%
“…Since then, research on tourism eco-efficiency began to expand and cover various perspectives [12]. Scholars mostly focus on measuring tourism eco-efficiency [13,14] and its influencing mechanisms [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, at the firm (industry) level, Fan et al (2022) measured the EE of real estate development using the super-SBM model and showed that the overall efficiency of 108 cities in the Yangtze River Economic Belt improved from 2006 to 2020. Zhang, Yang, Wu, et al (2022) used a similar approach to measure the EE of China's tourism industry and showed that it is generally in a stage of dynamic equilibrium. To assess the EE of the mining industry in 30 Chinese provinces, Zuo et al (2022) used a two-stage super-SBM model, and they found that the EE of the mining industry was higher in Western China than in other regions.…”
Section: Eco-efficiencymentioning
confidence: 99%
“…The increase of urbanization rate has significant heterogeneity for regions, and the urbanization rate is higher in the eastern region and central region at the present stage. Further increasing the level of urbanization rate will raise the level of production of carbon emissions, so the transformation of new urbanization should be accelerated, and new urbanization should play an important role in revitalizing the economy, while being a key step in the coordinated development of economic and ecological environments [77]. Therefore, new-type urbanization should be strengthened, especially in the eastern region and central region, to eliminate the high pollution and carbon emissions brought by traditional urbanization construction.…”
Section: Policy Suggestionsmentioning
confidence: 99%